Dependence of pedestal properties on plasma parameters. (29th November 2017) - Kim, S.K.; Na, Y.-S.; Saarelma, S.; Kwon, O.
Abstract: We have numerically investigated the dependence of pedestal properties such as the pedestal height and the pedestal width on various global parameters using the EURO-DEMO as the reference equilibrium. We have used EPED, a predictive model of the edge pedestal. Among global parameters, we have chosen to vary the triangularity, δ, the elongation, κ, and the poloidal beta, β p, which have larger effects on the pedestal properties. Improvement of pedestal properties can be achieved for more shaped plasma boundary. However, the increase in the pedestal height and the width with δ saturates around δ ∼ 0.6. Also, the pedestal width saturates and the pedestal temperature starts to decrease for κ > 1.9 . Improvement of the pedestal properties due to δ is larger at higher poloidal beta. The pedestal width slightly increases with the electron density at the pedestal top and the effective charge number.